Biological Risks and Laboratory-Acquired Infections: A Reality That Cannot be Ignored in Health Biotechnology - Coelho, Ana Cláudia; García Díez, Juan (Frontiers in Bioengineering and Biotechnology, 2015)
Advances and research in biotechnology have applications over a wide range of areas, such as microbiology, medicine, the food industry, agriculture, genetically modified organisms, and nanotechnology, among others. However, research with pathogenic agents, such as virus, parasites, fungi, rickettsia, bacterial microorganisms, or genetic modified organisms, has generated concern because of their potential biological risk – not only for people, but also for the environment due to their unpredictable behavior. In addition, concern for biosafety is associated with the emergence of new diseases or re-emergence of diseases that were already under control. Biotechnology laboratories require biosafety measures designed to protect their staff, the population, and the environment, which may be exposed to hazardous organisms and materials. Laboratory staff training and education is essential, not only to acquire a good understanding about the direct handling of hazardous biological agents but also knowledge of the epidemiology, pathogenicity, and human susceptibility to the biological materials used in research. Biological risk can be reduced and controlled by the correct application of internationally recognized procedures such as proper microbiological techniques, proper containment apparatus, adequate facilities, protective barriers, and special training and education of laboratory workers. To avoid occupational infections, knowledge about standardized microbiological procedures and techniques and the use of containment devices, facilities, and protective barriers is necessary. Training and education about the epidemiology, pathogenicity, and biohazards of the microorganisms involved may prevent or decrease the risk. In this way, the scientific community may benefit from the lessons learned in the past to anticipate future problems.